KAJIAN TERHADAP PELAKSANAAN SELF DECLARE SERTIFIKASI HALAL PADA PRODUK PANGAN BAGI KONSUMEN BERDASARKAN HUKUM POSITIF DI INDONESIA - Zahranissa Putri Faizal; Jeane Neltje Saly (Jurnal Hukum Adigama, 2022)
“This study aims to find out (1) how the implementation self declare halal certification for food products for consumers based on positive law in Indonesia, and (2) what are the obstacles to implementation self declare halal certification. This research is descriptive with qualitative analysis techniques using data collection methods in the form of literature studies (library research). Since the enactment of the Job Creation Law, several provisions from the previous laws and regulations have been amended, added, and deleted. One of them is changing and adding several provisions in Law Number 33 of 2014 concerning Guarantees for Halal Products. In the Job Creation Law added an article in Law Number 33 of 2014 concerning Guarantees for Halal Products regarding the concept self declare halal certification for Micro and Small Enterprises (UMK) actors as stated in Article 48 point 1 of the Job Creation Law. Basically self-declaring halal certification aims to provide convenience for Micro, Small and Medium Enterprises (UMK) actors in terms of business establishment permits, one of which is to provide convenience in obtaining halal certification. However, based on the research results, it is known that there are still obstacles in implementing self-declare halal certification which causes legal uncertainty for consumers. The solution to overcoming existing obstacles is to optimize product supervision and conduct outreach evenly to all Micro and Small business actors.